Twilight saga. 2, New moon - Meyer, Stephenie, 1973- (New York : Little, Brown and Co., 2006)
When the Cullens, including her beloved Edward, leave Forks rather than risk revealing that they are vampires, it is almost too much for eighteen-year-old Bella to bear, but she finds solace in her friend Jacob until he is drawn into a "cult" and changes in terrible ways.
Party -- Stitches -- The end -- Waking up -- Cheater -- Friends -- Repetition -- Adrenaline -- Third wheel -- The meadow -- Cult -- Intruder -- Killer -- Family -- Pressure -- Paris -- Visitor -- The funeral -- Race -- Volterra -- Verdict -- Flight -- The truth -- Vote -- Epilogue: Treaty.
"Megan Tingley books.".
690
Keywords: Vampires -- Fiction; Werewolves -- Fiction; High schools -- Fiction; Schools -- Fiction; Vampires -- Juvenile fiction; Werewolves -- Juvenile fiction; High schools -- Juvenile fiction; Schools -- Juvenile fiction; School stories; Washington (State) -- Fiction; Washington (State) -- Juvenile fiction; Young adult fiction; Detective and mystery fiction; Horror fiction; Young adult fiction; Romance fiction; Fantasy fiction; Paranormal fiction; Horror fiction; Fiction; Juvenile works; Young adult works; Paranormal romance; Paranormal fiction; Horror fiction